Quality of Reused Cooking Oil of Food Stalls in the Area of Muangsrikri Municipality, Warinchamrab, Ubon Ratchathani - Thanusin, Sudarat; Limpiteeprakan, Pawena; Lapkham, Chiraporn; Manwong, Mereerat (Health Science Journal of Thailand, 2021)
This research amied to study the knowledge, behavior of food vendors, and quality of reused cooking oil from 52 food stalls in Muang Si Khai Subdistrict Municipality, Warin Chamrap District, Ubon Ratchathani Province. The data was gathered using a questionnaire and testing the oil quality. Data was analyzed using descriptive statistics such as frequency, percentage, mean, standard deviation, minimum and maximum value. The study was conducted during May 2019. Results revealed that knowledge about the use of frying oil was rated at a low level (40.4%). The food stalls owners still do not know that reusing oil to fry food is illegal at 75.0%. Most of them use oil to fry food more than once, 96.2%. The most used is vegetable oil at 94.2%, of which 76.9% is palm oil. Frying pans used were aluminum at 42.3%. The results of the total polar compound analysis in fried oil of food stalls found that there 6 stalls did not pass the standard criteria, representing 11.5%, with the range of 25.2-27.2 % by weight. Therefore, municipalities should control and monitor the standard of repeat frying oil in food stalls with increasing frequency of regular frying oil quality measurement.